Viability and Inhibition of Endophytic Bacteria Pseudomonas fluorescens 4RS1 Against Phytophthora palmivora in Flour Formula - Khaeruni, Andi; Hariyani; Hisein, Waode Siti Anima; Satrah, Vit Neru; Wijayanto, Teguh; Sutariati, Gusti Ayu Kade; Taufik, Muhammad (Jurnal Fitopatologi Indonesia, 2022)
Viability and Inhibition of Endophytic Bacteria Pseudomonas fluorescens 4RS1 Against Phytophthora palmivora in Flour Formula Pseudomonas fluorescens 4RS1 is an endophytic bacterium that has good inhibition against Phytophthora palmivora, and it has the potential to be developed as a biological agent for black pod rot disease in cocoa. It is necessary to have a formulation that can maintain viability and inhibition and facilitate its use and application, to apply this bacterial agent at the farm level. This study aimed to determine the ability of talc and tapioca flour as the ingredients of formulations that have strong solubility and maintain the viability and inhibition of P. fluorescens 4RS1. The results showed that the use of tapioca flour as the basis for the formulation of P. fluorescens 4RS1 was better than talc because it had high solubility and low precipitation. The addition of nutrients in the form of brown sugar, peptone, and CMC in the tapioca flour formulation was able to maintain the viability and inhibition of P. fluorescens 4RS1 for 12 weeks of storage.